Do low interest rates sow the seeds of financial crises? - Simona E. Cociuba; Malik Shukayev; Alexander Ueberfeldt (The University of Western Ontario, Economic Policy Research Institute (EPRI), 2012)
A view advanced in the aftermath of the late-2000s financial crisis is that lower than optimal interest rates lead to excessive risk taking by financial intermediaries. We evaluate this view in a quantitative dynamic model where interest rate policy affects risk taking by changing the amount of safe bonds available as collateral for repo transactions. Given properly priced collateral, lower than optimal interest rates reduce risk taking. However, if intermediaries can augment their collateral by issuing assets whose risk is underestimated by rating agencies, lower than optimal interest rates contribute to excessive risk taking and amplify the severity of recessions.
Keywords: E44; E52; G28; D53; 330; financial intermediation; risk taking; optimal interest rate policy; capital regulation; Geldpolitik; Zinspolitik; Bankgeschäft; Risikofreude; Finanzmarktkrise; Theorie